2015
DOI: 10.1016/j.cegh.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Social health problem of adolescent girls aged 15–19 years living in slums of Dibrugarh town, Assam

Abstract: c l i n i c a l e p i d e m i o l o g y a n d g l o b a l h e a l t h 3 ( 2 0 1 5 ) s 4 9 -s 5 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 6 publications
2
10
0
Order By: Relevance
“…Living with guardians instead of own parents was associated with thinness only in one study, and an increasing number of servants in a household was associated with decreased prevalence of stunting . Furthermore, two studies showed that adolescents living in joint families were more likely to be stunted or thin . Similar to migration at the individual level, adolescents living in households who migrated from a rural to an urban area in Senegal had higher WHZ and WAZ than those who did not migrate .…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Living with guardians instead of own parents was associated with thinness only in one study, and an increasing number of servants in a household was associated with decreased prevalence of stunting . Furthermore, two studies showed that adolescents living in joint families were more likely to be stunted or thin . Similar to migration at the individual level, adolescents living in households who migrated from a rural to an urban area in Senegal had higher WHZ and WAZ than those who did not migrate .…”
Section: Resultsmentioning
confidence: 95%
“…Education is often mentioned in relation to nutritional status. School attendance and enrollment, educational and literacy levels were in general negatively associated with stunting, underweight, and thinness and positively with HA, WA, and WHZ . One Tanzanian study, however, found that school nonenrollment was associated with increased thinness explaining this by the fact that parents often perceived thin adolescents as physically not being ready to attend school …”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations